2021
DOI: 10.1186/s13102-021-00257-5
|View full text |Cite
|
Sign up to set email alerts
|

Random forest model to identify factors associated with anabolic-androgenic steroid use

Abstract: Background One of the types of doping that is commonly used by bodybuilders, is androgenic-anabolic steroids (AAS). The use of AAS besides violating sporting ethics would have serious consequences on physical and mental health statuses. This study aimed to determine the most important factors of using AAS among bodybuilders by prototype willingness model (PWM). Methods In this analytical cross-sectional study, 280 male bodybuilders were selected fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…AASs are synthetic substances related to male sex hormones that affect skeletal muscle growth and male sexual development (2). The use of AAS has also been shown to cause side effects such as infertility, sexual dysfunction, edema, hair growth disorders, acne, liver problems, testicular shrinkage, myocardial infarction, left ventricular hypertrophy, cardiac dysentery, pulmonary embolism (3,4), and personality and behavioral disorders (5). Bijeh et al evaluated the knowledge, prevalence, and side effects of AAS in athletes; they reported that lack of knowledge about the side effects of AAS, dissatisfaction with body type, the hope of winning competitions and receiving sports titles, pressure and emphasis of coaches, and attempts to attract the attention of others were the most critical factors related to drug use and AAS (6).…”
Section: Introductionmentioning
confidence: 99%
“…AASs are synthetic substances related to male sex hormones that affect skeletal muscle growth and male sexual development (2). The use of AAS has also been shown to cause side effects such as infertility, sexual dysfunction, edema, hair growth disorders, acne, liver problems, testicular shrinkage, myocardial infarction, left ventricular hypertrophy, cardiac dysentery, pulmonary embolism (3,4), and personality and behavioral disorders (5). Bijeh et al evaluated the knowledge, prevalence, and side effects of AAS in athletes; they reported that lack of knowledge about the side effects of AAS, dissatisfaction with body type, the hope of winning competitions and receiving sports titles, pressure and emphasis of coaches, and attempts to attract the attention of others were the most critical factors related to drug use and AAS (6).…”
Section: Introductionmentioning
confidence: 99%
“…The second part included 42 questions on constructs of PWM, which had six sub-scales. The structure of the PWM questionnaire was adapted, so the results of other studies that evaluated health behaviors in Iran based on PWM were used ( Rahimi and Javadi, 2018 ; Mirzaie Alavijeh et al, 2019 ; Bashirian et al, 2020 ; Manoochehri et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The findings indicate that, in comparison to the social reaction path, the reasoned action path has a stronger impact on predicting the use of AAS among bodybuilders. [4].…”
Section: Random Forest Model To Identify Factors Associated With Anab...mentioning
confidence: 99%